2008
DOI: 10.1007/s10531-008-9533-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Odonata (Insecta) assemblages along an altitudinal gradient in the sierra de Coalcomán Mountains, Michoacán, Mexico

Abstract: Odonate diversity in the Coalcomán Mountain Range (CMR), Michoacán State, Mexico, was surveyed, and samplings were made during 2 years in eight streams along an altitudinal gradient. Presence-absence data were analyzed using non-parametric and parametric methods. Beta and gamma diversities were estimated using Whittaker's and Lande's formulae, respectively. A total of 2,526 adults and 489 larvae were captured, yielding 116 species (c diversity), 44 genera and 9 families. Five new species were discovered. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
2
20
0
2
Order By: Relevance
“…Most species showed a restricted distribution in the CM, which suggests a high turnover rate, a conclusion supported by the fact that most of the Bray-Curtis paired similarities were smaller than 25%. Hence, beta diversity is an important component of gamma diversity among these sites (Novelo-Gutiérrez & Gómez-Anaya 2009). Our results also support the betadiverse Mexico hypothesis (Arita & León-Paniagua 1993, Sarukhán et al 1996, a result of high environmental heterogeneity in the CM.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most species showed a restricted distribution in the CM, which suggests a high turnover rate, a conclusion supported by the fact that most of the Bray-Curtis paired similarities were smaller than 25%. Hence, beta diversity is an important component of gamma diversity among these sites (Novelo-Gutiérrez & Gómez-Anaya 2009). Our results also support the betadiverse Mexico hypothesis (Arita & León-Paniagua 1993, Sarukhán et al 1996, a result of high environmental heterogeneity in the CM.…”
Section: Discussionsupporting
confidence: 89%
“…The sampled streams included Ticuiz (TZ), Estanzuela (EZ), Río Pinolapa (RP), Colorín (CL) and Chichihua (CH). Details on water channels and averages of physicochemical data for the streams have been published by Novelo-Gutiérrez & Gómez-Anaya (2009), and are summarized in Table 1.…”
Section: Study Areamentioning
confidence: 99%
“…Libellulidae gathers most of Odonata species with wider distribution and richness (Costa et al, 2000;Novelo-Gutiérrez and Gómez-Anaya, 2009), which was also verified in the present study. One characteristic of this family is the largest body size of individuals that increases the dispersal ability (Dalzochio et al 2011), and thus the species distribution in streams.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the Highland Grasslands are located in areas of higher altitude (up to 1000 m) in RS (Oliveira-Filho & Fontes 2000, Cordeiro & Hasenack 2009, IBGE 2012, where temperature can reach low values. Previous studies showed that elevation gradients as well as forest and open landscapes can largely influence the regional richness and composition of Odonata (Novelo-Gutiérrez & Gómez-Anaya 2009, Renner et al 2019. In this sense, such environmental differences in vegetation type and elevation could have accounted for the differences in odonate composition here observed between the Seasonal Deciduous Forest and the Highland Grasslands.…”
Section: Checklist Of Odonata In the Seasonal Deciduous Forest And Prmentioning
confidence: 57%